Highlights from the 2019 European Congress on Treatment and Research in Multiple Sclerosis (ECTRIMS 2019). (June 2020) - Lünemann, Jan D; Diaz-Diaz, Judit; Stankoff, Bruno; Young, Carolyn; Siva, Aksel; Miller, Aaron; Lubetzki, Catherine; Wiendl, Heinz; Oreja-Guevara, Celia
The 2019 ECTRIMS Congress, in Stockholm, has had record-breaking figures for both attendance and scientific production. There were 9361 participants from 100 different countries for a total of 1541 abstracts. Upon invitation of the European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS) executive committee, the authors of this meeting report assessed abstracts from all poster and oral presentations for novelty, scientific quality and relevance for basic and clinical multiple sclerosis (MS) research. The objective of this report is to highlight a selection of basic, translational and clinical studies out of the many outstanding projects that were presented. Abstracts and references cited in our report were chosen at the discretion of the authors and all co-authors and the ECTRIMS executive committee agreed on the selection. In the event of discrepancies between the abstract and the uploaded poster or presentation, we aimed to present data derived from the poster or presentation. All abstracts are accessible through the ECTRIMS online library (https://onlinelibrary.ectrimscongress.eu/ectrims/#!*menu=36*browseby=3*sortby=2*ce_id=160 ) and also published in this journal (Volume 25 Issue 2_suppl, September 2019;https://journals.sagepub.com/toc/msja/25/2_suppl ). A few additional references from the literature were added but were restricted to the ones that authors considered as absolutely required for an optimized understanding of the topics highlighted.